Diagnosis of complex breast cysts using X-ray pneumocystography and endoscopic mammocystoscopy - O.A. Aksonov (Publishing House TRILIST, 2022)
Background. Complex cysts of the breast (CCB), in contrast to simple and complicated cysts, are characterized by a high (up to 31.0%) oncological potential. Mammography and ultrasound (US) as the most common methods of radiological diagnosis do not allow to classify CCB on benign and malignant, and in the case of breast cancer (BC) are not detected the establishment of its molecular genetic subtype. Objectives: to analyze and popularize own experience of using endoscopic mammocystoscopy (EMCS) and X-ray pneumocystography (RPCG) for the diagnosis of CCB and biopsy navigation. Materials and methods. The clinical and anamnestic data, the results of radiological, endoscopic and pathomorphological studies in 286 adult women with simple, complicated breast cysts and CCB were analyzed (n = 45, 134 and 142, respectively). Results. The diagnostic and navigation capabilities of US are limited by frequent (18.1%) false-negative results, which are caused by atypical echosemiotics of CCB. Trepan-biopsy under US control becomes impossible when visualization of the CCB disappears, which often occurs during fine-needle aspiration of the liquid component. Technical difficulties arise when imitating a puncture needle with linear hyperechoic structures induced by Cooper's ligaments, as well as when positioning the CCB in a bulky, non-fixed gland. In terms of diagnostic specificity and prognostic significance of a negative result, RPCG is slightly (5.6 and 4.7%, respectively) inferior to US and in certain clinical situations it can be used to assess the likelihood of BC, and in case of positive results for navigate a stereotaxic сore needle biopsy. EMCS is a low-traumatic procedure that provides direct visual contact with intracystic neoplasms, allows assessing the probability of BC and conducting a pinch biopsy. Conclusions. The consistent combined use of well-known and author's methods with the involvement of US, RPCG and EMCS according to the given algorithm ensures effective management of CCB at the modern level.